Is the First of the Two Born Saved? A Rare and Dramatic Case of Double Placental Damage from SARS-CoV-2 - Leonardo Resta; Antonella Vimercati; Sara Sablone; Andrea Marzullo; Gerardo Cazzato; Giuseppe Ingravallo; Giulia Mazzia; Francesca Arezzo; Anna Colagrande; Roberta Rossi (Viruses, 2021)
The current coronavirus pandemic has affected, in a short time, various and different areas of medicine. Among these, the obstetric field has certainly been touched in full, and the knowledge of the mechanisms potentially responsible for placental damage from SARS-CoV-2 occupy a certain importance. Here we present here a rare case of dichorionic twins born at 30 weeks and 4 days of amenorrhea, one of whom died in the first few hours of life after placental damages potentially related to SARS-CoV-2. We also propose a brief review of the current literature giving ample emphasis to similar cases described.